INTERNET MARKETING UNTUK MENINGKATKAN JARINGAN PEMASARAN PADA USAHA SANTRI PONDOK PESANTREN SALAF AL- QUR’AN (PPSQ) ASY-SYADZILI - Fatimah, Annisa (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2021)
The purpose of this PKM activity to provide knowledge sharing related to internet marketing to increase marketing in the Salaf Al-Qur'an Islamic Boarding School (PPSQ) Asy-Syadzili, Pakis Kembar, Malang. The first step for this program is to open the mind of the students that potential market for entrepreneurs for them is v widely. Marketing strategies continue to evolve from traditional marketing methods to modern methods. Taking the benefits by integrating this two methods to find the optimal point in marketing the products of students is very important to optimize sales of products that have been produced by students. It has been coordinated with the Pondok Pesantren Salaf Al-Qur'an (PPSQ) Asy-Syadzili, Pakis Kembar, Malang which will host the PKM activities by inviting all students. The presence of lecturers and students who are also entrepreneurial practitioners are expected to provide enlightenment and new knowledge that is quite meaningful for all participants.